A Qualitative Exploration of Return to Work in the First 3-Years After Serious Injury. Issue 12 (December 2019) - Braaf, Sandra; Collie, Alex; Ameratunga, Shanthi; Harrison, James; Teague, Warwick; Cameron, Peter; Christie, Nicola; Gabbe, Belinda
Abstract : Objective: To explore how people with serious injuries returned to paid employment in the first 3-years after injury. Methods: Fifty-four adult survivors of serious injuries were interviewed at 3-years post-injury, all of whom had returned to work and were currently employed. A framework analysis approach was undertaken. Results: Participant decisions and actions taken to return to work (RTW) were influenced by their resilience, approach to adjusting goals, priorities and plans, and how social connections and relationships were used and maintained. The environment in which these decisions and actions were taken shaped opportunities for work in meaningful, appropriate, and sustained employment. Conclusions: Our study of 54 people who RTW indicated the importance of personal adjustments and resources, positive social relations, and advanced planning aligning with responsive employers, insurers and health professionals for successful RTW. Abstract : Supplemental Digital Content is available in the text